Modified molybdenum disulfide / carbon-based composite material as well as preparation method and application thereof
By embedding low-defect MoS2 in the entangled carbon-based material and covering the hydrophilic polymer, the problem of insufficient flexibility and stability of the electrocatalytic material is solved, and the flexibility of the modified molybdenum disulfide/carbon-based composite material is improved and Electrochemical catalytic performance improves hydrogen production efficiency and photo-assisted electrocatalytic reaction efficiency.
Patent Information
- Application Number
- CN202411512492.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2024-12-13
AI Technical Summary
The existing electrocatalytic materials have shortcomings in flexibility and stability, resulting in a degradation in performance in different shapes and structures. In particular, the composite materials of molybdenum disulfide and carbon-based materials have poor flexibility and are prone to fall off, affecting the electrochemical catalytic performance.
The modified molybdenum disulfide/carbon-based composite is prepared by ultrasonic mixing and drying to improve its flexibility and stability and enhance its flexibility and stability. Electrocatalytic activity and conductivity.
Significantly improves the flexibility and electrochemical catalytic properties of the modified molybdenum disulfide/carbon-based composite material, enhances hydrogen production efficiency and photo-assisted electrocatalytic reaction efficiency, improves the self-supporting and durability of the material, and reduces the self-supporting film. The contact angle increases the active surface area and improves the overall hydrogen production performance.
Smart Images

Figure CN119121292A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of light-assisted electrocatalysis, and specifically relates to a modified molybdenum disulfide / carbon-based composite material and a preparation method and application thereof. Background Art
[0002] With the intensification of the global energy crisis and environmental pollution problems, it has become particularly important to develop new, efficient and environmentally friendly energy materials. Electrocatalysis technology has attracted widespread attention due to its wide application in energy conversion and storage, environmental protection and other fields. Light-assisted electrocatalysis technology combines the advantages of photocatalysis and electrocatalysis. It promotes the electrocatalytic reaction by photoexciting electron-hole pairs, increases the reaction rate and reduces energy consumption. It is a very promising green chemical technology. In addition, with the rapid development of flexible electronics and wearable devices, the demand for flexible electrocatalytic materials is growing, which requires the materials to maintain their performance in different shapes and structures.
[0003] Although existing electrocatalytic materials have made significant progress in some aspects, they still have some limitations, such as poor conductivity, insufficient stability, and few active sites. Therefore, the development of new high-performance electrocatalytic materials remains a challenge.
[0004] In the study of electrocatalytic materials, transition metal sulfides such as molybdenum disulfide and carbon-based materials such as carbon nanotubes are favored by researchers because of their unique physical and chemical properties. MoS2 has excellent electrocatalytic activity, but in practical applications, it has problems such as poor electrical conductivity and few active sites. Carbon nanotubes can significantly improve the electrical conductivity and mechanical properties of composite materials with their excellent mechanical strength, electrical conductivity and thermal conductivity. The prior art directly uses MoS2 and carbon-based materials to prepare composite materials. Because both MoS2 and carbon-based materials are rigid materials, the resulting composite materials have poor flexibility and are easy to fall off and crack after film formation, which affects its mass transfer process in the electrolyte, resulting in poor electrochemical catalytic performance of the composite materials. Summary of the invention
[0005] The present invention provides a modified molybdenum disulfide / carbon-based composite material and a preparation method and application thereof, which solves the problem that the prior art directly uses MoS2 and carbon-based materials to prepare composite materials. Since both MoS2 and carbon-based materials are rigid materials, the prepared composite materials have poor flexibility and are prone to fall off and crack after film formation, which affects the mass transfer process in the electrolyte and leads to poor electrochemical catalytic performance of the composite materials.
[0006] The first aspect of the present invention provides a modified molybdenum disulfide / carbon-based composite material, comprising:
[0007] Entangled carbon-based materials;
[0008] Low-defect MoS2 is embedded inside and on the surface of the entangled carbon-based material, and the surface of the entangled carbon-based material is partially coated with a hydrophilic polymer.
[0009] The second object of the present invention is to provide a method for preparing a modified molybdenum disulfide / carbon-based composite material, comprising:
[0010] After the low-defect MoS2 and the entangled carbon-based material are evenly mixed, a hydrophilic polymer solution is added, and after stirring at room temperature for 30 minutes, the modified molybdenum disulfide / carbon-based composite material is obtained by drying.
[0011] Preferably, the mass ratio of MoS2:entangled carbon-based material:hydrophilic polymer is 1:9:1.
[0012] By controlling the amount of hydrophilic polymer added, the degree of hydrophilic polymer coating on the carbon substrate and the flexibility of the modified molybdenum disulfide / carbon-based composite material can be controlled. If the amount of hydrophilic polymer added is too large, the hydrophilic polymer completely coats the entangled carbon-based material, the MoS2 active sites are covered and cannot react; if the amount of hydrophilic polymer added is too small, the flexibility of the modified molybdenum disulfide / carbon-based composite material is too poor, and it is easy to fall off and crack after film formation, affecting the hydrogen production performance.
[0013] Preferably, the hydrophilic polymer is polyacrylic acid, polyethylene glycol, polyvinyl alcohol, or polyethylene glycol maleic anhydride ester.
[0014] Preferably, the entangled carbon-based material is acidified carbon nanotubes, carbon cloth or carbon paper.
[0015] Preferably, the preparation method of the low-defect MoS2 is:
[0016] In a nitrogen atmosphere, MoS2 is annealed at 300-500°C for 1-3h to obtain the low-defect MoS2.
[0017] Preferably, the gas flow rate of the nitrogen is 10 to 30 mL / min.
[0018] Preferably, the preparation method of MoS2 is:
[0019] After dissolving ammonium molybdate tetrahydrate and thiourea, react at 160-200°C for 24 hours. After cooling to room temperature, wash the product with ethanol and water and vacuum dry it at 60°C for 12 hours to obtain MoS2.
[0020] Preferably, the mass ratio of ammonium molybdate tetrahydrate to thiourea is 1-1.4:2-2.4.
[0021] Preferably, the low-defect MoS2 and the entangled carbon-based material are ultrasonically mixed, and the ultrasonic conditions are: 30 to 45 minutes.
[0022] The third object of the present invention is to protect the application of the molybdenum disulfide / carbon-based composite material in light-assisted electrocatalytic hydrogen production.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The modified molybdenum disulfide / carbon-based composite material provided by the present invention improves the flexibility and stability of the modified molybdenum disulfide / carbon-based composite material by embedding low-defect MoS2 inside and on the surface of the entangled carbon-based material, and the surface of the entangled carbon-based material is partially coated with a hydrophilic polymer. Since the entangled carbon-based material itself is entangled, low-defect molybdenum sulfide can be fixed inside it, enhancing affinity and improving its stability with carbon nanotubes. At the same time, the entanglement method increases the loading amount of molybdenum disulfide; the more molybdenum sulfide, the better the electrocatalytic hydrogen production performance, but a large amount of molybdenum sulfide is easy to accumulate and agglomerate. The method of entangled carbon-based material entangled and fixed molybdenum sulfide can prevent its agglomeration while fixing a large amount of molybdenum sulfide. The hydrophilic polymer in the modified molybdenum disulfide / carbon-based composite material partially coats the entangled carbon-based material and molybdenum sulfide. Since the entanglement density of the entangled carbon-based material itself is high, the physical structure is relatively stable; at the same time, the physical coating of the hydrophilic polymer itself can improve stability. The present invention has been found through research that the electrochemical catalytic performance of metal sulfide / entangled carbon-based materials is closely related to the surface hydrophilicity and hydrophobicity they possess. In the first aspect, the modified molybdenum disulfide / carbon-based composite material provided by the present invention improves the hydrophilicity and hydrophobicity of the material after the hydrophilic polymer partially coats the MoS2 / entangled carbon-based material, reduces the solvent contact angle, enables the solvent to fully infiltrate the system, better utilizes the active surface area of the modified molybdenum disulfide / carbon-based composite material, enhances the film-forming property of the system, reduces the contact angle of the self-supporting film of the modified molybdenum disulfide / carbon-based composite material, improves the surface hydrophilicity and hydrophobicity, thereby bringing a larger contact area and mass transfer rate, so that the overall hydrogen production performance has been significantly increased; at the same time, a large amount of gas will be generated during the reaction process, and since the modified molybdenum disulfide / carbon-based composite material has good wettability, the reaction solution can re-enter after the gas is discharged, and continue to react with the modified molybdenum disulfide / carbon-based composite material, and hydrogen can be continuously produced. Taking the PAA-modified MoS2 / carbon nanotube composite film as an example, under illumination, at the same potential (180mV), the overall hydrogen production efficiency of the PAA-modified MoS2 / carbon nanotube composite film is about 40% higher than that of the MoS2 / carbon nanotube composite film. On the second hand, the PAA-modified MoS2 / carbon nanotube composite film provided by the present invention further increases light absorption compared with the MoS2 / carbon nanotube composite film, and can absorb light in a wider wavelength range, which is crucial for improving the efficiency of light-assisted electrocatalytic reactions; on the third hand, the MoS2 / carbon nanotube composite material provided by the prior art has relatively large rigidity, poor film-forming properties, and is easy to fall off and crack after film formation; the modified molybdenum disulfide / carbon-based composite material provided by the present invention adds flexible linking points in the rigid carbon-based material, so that the system has better flexibility, is not easy to crack after bending, and can complete the construction of self-supporting material electrodes.
[0025] 2. The present invention first anneals MoS2 to prepare low-defect MoS2, which has a larger band gap, reduces molybdenum sulfide defects, enhances affinity, can improve the material's absorption of light in a larger wavelength range, and provide greater photoelectric synergistic conversion performance; then, by compounding low-defect MoS2, entangled carbon-based materials and hydrophilic polymers, the electrocatalytic activity, flexibility, conductivity and stability of the material are improved. The preparation method provided by the present invention is simple, low-cost, and easy to mass produce. At the same time, the prepared modified molybdenum disulfide / carbon-based composite material is easy to process into a desired shape, which makes it highly feasible in industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a transmission electron microscope image of the modified molybdenum disulfide / carbon-based composite material obtained in Example 1 of the present invention after secondary ultrasonic dispersion;
[0027] Figure 2 The Raman spectra of the modified molybdenum disulfide / carbon-based composite material prepared in Example 1 of the present invention, the MoS2 / carbon nanotubes and carbon nanotubes prepared in Comparative Example 1;
[0028] Figure 3 Infrared spectra of composite materials prepared for different groups;
[0029] Figure 4 The contact angles of the self-supporting films of the acidified CNTs pressed film (a), PEG-modified MoS2 / CNTs composite film, PAA-modified MoS2 / CNTs composite film (c), PVA-modified MoS2 / CNTs composite film (d), and PEM-modified MoS2 / CNTs composite film (e);
[0030] Figure 5 This is a physical picture of the PAA-modified MoS2 / carbon nanotube composite film;
[0031] Figure 6 This is a flexibility test image of the PAA-modified MoS2 / carbon nanotube composite film;
[0032] Figure 7 The Tafel plot of electrocatalytic hydrogen evolution of PAA-modified MoS2 / carbon nanotube composite film in 1M KOH;
[0033] Figure 8 Photoresponse diagram of PAA-modified MoS2 / carbon nanotube composite film and MoS2 / carbon nanotube composite material. DETAILED DESCRIPTION
[0034] The technical solutions in the present invention will be described clearly and completely below in conjunction with the specific implementation of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] The methods described in the embodiments of the present invention are conventional methods unless otherwise specified. The materials, reagents, etc. used can be obtained from commercial sources unless otherwise specified.
[0036] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. Among them, A and B can be singular or plural; the single symbol " / " means "or".
[0037] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of A, B or C", or "at least one of A, B and C" can represent any one of A, B, C, or A+B, or A+C, or B+C, or A+B+C, where A, B, C can be single or multiple, respectively.
[0038] In the following description of this embodiment, the order of serial numbers does not mean the order of execution. Some or all of the steps can be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of this embodiment.
[0039] In the following description of the present embodiment, the numerical range should be understood to also specifically disclose each intermediate value between the upper and lower limits of the range. Any stated value or intermediate value in the stated range and any other stated value or each smaller range between the intermediate values in the stated range are also included in the present embodiment, and the upper and lower limits of the smaller range can be independently included or excluded in the range.
[0040] Unless otherwise stated, the technical / scientific terms used in the present embodiment have the same meanings as those generally understood by those skilled in the art to which the present application belongs. Although the present application only describes preferred methods and materials, any similar or equivalent methods and materials may also be used in the implementation or testing of the present application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of any conflict with any incorporated document, the content of this specification shall prevail.
[0041] Abbreviations of some raw materials in the examples and comparative examples of the present invention:
[0042] Polyacrylic acid: PAA, polyethylene glycol: PEG, polyvinyl alcohol: PVA, polyethylene glycol maleic anhydride ester: PEM.
[0043] Example 1
[0044] A method for preparing a modified molybdenum disulfide / carbon-based composite material comprises the following steps:
[0045] S1. Dissolve ammonium molybdate tetrahydrate and thiourea in water, stir evenly, and transfer to a high-pressure reactor. React at 180°C for 24 hours. After cooling to room temperature, wash the product with ethanol and water and vacuum dry it at 60°C for 12 hours to obtain MoS2 powder.
[0046] Wherein, the mass ratio of ammonium molybdate tetrahydrate: thiourea: water is 1.2:2.2:35.
[0047] S2. Preparation of low-defect MoS2: In a tubular furnace, under a nitrogen atmosphere, the temperature was 400°C, the gas flow rate was 20 mL / min, and the annealing time was 2 h.
[0048] S3. The low-defect MoS2 and the acidified carbon nanotubes were uniformly dispersed by ultrasonication with ethanol, and polyacrylic acid was dissolved in water. Then the polyacrylic acid solution was slowly poured into the mixed dispersion of MoS2 and the acidified carbon nanotubes. After stirring at room temperature for 30 minutes, the PAA-modified MoS2 / carbon nanotube dispersion was obtained.
[0049] Among them, the mass ratio of MoS2:PAA:acidified carbon nanotubes is 1:1:9, and the specific amounts of the three are 0.1g, 0.1g, and 0.9g respectively; the amount of ethanol used is 40ml, and the amount of water used is 20ml; and the ultrasonic time is 30min.
[0050] S4. Pour the PAA-modified MoS2 / carbon nanotube dispersion onto a polytetrafluoroethylene surface dish and allow it to dry naturally at room temperature to obtain a flexible PAA-modified MoS2 / carbon nanotube composite film, i.e., a modified molybdenum disulfide / carbon-based composite material, denoted as CNTs / MoS2 / PAA.
[0051] Example 2
[0052] A method for preparing a modified molybdenum disulfide / carbon-based composite material comprises the following steps:
[0053] S1. Dissolve ammonium molybdate tetrahydrate and thiourea in water, stir evenly, and transfer to a high-pressure reactor. React at 160°C for 24 hours. After cooling to room temperature, wash the product with ethanol and water and vacuum dry it at 60°C for 12 hours to obtain MoS2 powder.
[0054] Among them, the mass ratio of ammonium molybdate tetrahydrate:thiourea:water is 1.2:2.2:35.
[0055] S2. Preparation of low-defect MoS2: In a tubular furnace, under nitrogen atmosphere, the temperature is 300°C, the gas flow rate is 10 mL / min, and the annealing time is 1 h.
[0056] S3. The low-defect MoS2 and the acidified carbon nanotubes were uniformly dispersed by ultrasonication with ethanol, and polyacrylic acid was dissolved in water. Then the polyacrylic acid solution was slowly poured into the mixed dispersion of MoS2 and the acidified carbon nanotubes. After stirring at room temperature for 30 minutes, the PAA-modified MoS2 / carbon nanotube dispersion was obtained.
[0057] Among them, the mass ratio of MoS2:PAA:acidified carbon nanotubes is 1:1:9, and the specific amounts of the three are 0.1g, 0.1g, and 0.9g respectively; the amount of ethanol used is 40ml, and the amount of water used is 20ml; and the ultrasonic time is 30min.
[0058] S4. Pour the PAA-modified MoS2 / carbon nanotube dispersion onto a polytetrafluoroethylene surface dish and allow it to dry naturally at room temperature to obtain a flexible PAA-modified MoS2 / carbon nanotube composite film, denoted as CNTs / MoS2 / PAA.
[0059] Example 3
[0060] A method for preparing a modified molybdenum disulfide / carbon-based composite material comprises the following steps:
[0061] S1. Dissolve ammonium molybdate tetrahydrate and thiourea in water, stir evenly, and transfer to a high-pressure reactor. React at 200°C for 24 hours. After cooling to room temperature, wash the product with ethanol and water and vacuum dry it at 60°C for 12 hours to obtain MoS2 powder.
[0062] Among them, the mass ratio of ammonium molybdate tetrahydrate:thiourea:water is 1.2:2.2:35.
[0063] S2. Preparation of low-defect MoS2: In a tubular furnace, under nitrogen atmosphere, the temperature is 400°C, the gas flow rate is 30 mL / min, and the annealing time is 3 h.
[0064] Among them, the temperature is 400°C, the gas flow rate is 20mL / min, and the annealing time is 2h.
[0065] S3. The low-defect MoS2 and the acidified carbon nanotubes were uniformly dispersed by ultrasonication with ethanol, and polyacrylic acid was dissolved in water. Then the polyacrylic acid solution was slowly poured into the mixed dispersion of MoS2 and the acidified carbon nanotubes. After stirring at room temperature for 30 minutes, the PAA-modified MoS2 / carbon nanotube dispersion was obtained.
[0066] Among them, the mass ratio of MoS2:PAA:acidified carbon nanotubes is 1:1:9, and the specific amounts of the three are 0.1g, 0.1g, and 0.9g respectively; the amount of ethanol used is 40ml, and the amount of water used is 20ml; and the ultrasonic time is 30min.
[0067] S4. Pour the PAA-modified MoS2 / carbon nanotube dispersion onto a polytetrafluoroethylene surface dish and allow it to dry naturally at room temperature to obtain a flexible PAA-modified MoS2 / carbon nanotube composite film, denoted as CNTs / MoS2 / PAA.
[0068] Example 4
[0069] A method for preparing a modified molybdenum disulfide / carbon-based composite material comprises the following steps:
[0070] S1. Dissolve ammonium molybdate tetrahydrate and thiourea in water, stir evenly, and transfer to a high-pressure reactor. React at 180°C for 24 hours. After cooling to room temperature, wash the product with ethanol and water and vacuum dry it at 60°C for 12 hours to obtain MoS2 powder.
[0071] Among them, the mass ratio of ammonium molybdate tetrahydrate:thiourea:water is 1.2:2.2:35.
[0072] S2. Preparation of low-defect MoS2: In a tubular furnace, under a nitrogen atmosphere, the temperature was 400°C, the gas flow rate was 20 mL / min, and the annealing time was 2 h.
[0073] S3. The low-defect MoS2 and acidified carbon nanotubes are uniformly dispersed by ultrasonic dispersion with ethanol, and PVA is dissolved in water. The PVA solution is then slowly poured into the mixed dispersion of MoS2 and acidified carbon nanotubes. After stirring at room temperature for 30 minutes, a PVA-modified MoS2 / carbon nanotube dispersion is obtained.
[0074] Among them, the mass ratio of MoS2:PVA:acidified carbon nanotubes is 1:1:9, and the specific amounts of the three are 0.1g, 0.1g, and 0.9g respectively; the amount of ethanol used is 40ml, and the amount of water used is 20ml; and the ultrasonic time is 30min.
[0075] S4. Pour the PVA-modified MoS2 / carbon nanotube dispersion onto a polytetrafluoroethylene surface dish and allow it to dry naturally at room temperature to obtain a flexible PVA-modified MoS2 / carbon nanotube composite film, denoted as CNTs / MoS2 / PVA.
[0076] Example 5
[0077] A method for preparing a modified molybdenum disulfide / carbon-based composite material comprises the following steps:
[0078] S1. Dissolve ammonium molybdate tetrahydrate and thiourea in water, stir evenly, and transfer to a high-pressure reactor. React at 180°C for 24 hours. After cooling to room temperature, wash the product with ethanol and water and vacuum dry it at 60°C for 12 hours to obtain MoS2 powder.
[0079] Among them, the mass ratio of ammonium molybdate tetrahydrate:thiourea:water is 1.2:2.2:35.
[0080] S2. Preparation of low-defect MoS2: In a tubular furnace, under a nitrogen atmosphere, the temperature was 400°C, the gas flow rate was 20 mL / min, and the annealing time was 2 h.
[0081] S3. The low-defect MoS2 and the acidified carbon nanotubes were uniformly dispersed by ultrasonication with ethanol, and PEG was dissolved in water. Then the PEG solution was slowly poured into the mixed dispersion of MoS2 and the acidified carbon nanotubes. After stirring at room temperature for 30 minutes, a PEG-modified MoS2 / carbon nanotube dispersion was obtained.
[0082] Among them, the mass ratio of MoS2:PEG:acidified carbon nanotubes is 1:1:9, and the specific amounts of the three are 0.1g, 0.1g, and 0.9g respectively; the amount of ethanol used is 40ml, and the amount of water used is 20ml; the ultrasonic time is 30min.
[0083] S4. Pour the PEG-modified MoS2 / carbon nanotube dispersion onto a polytetrafluoroethylene surface dish and allow it to dry naturally at room temperature to obtain a flexible PEG-modified MoS2 / carbon nanotube composite film, denoted as CNTs / MoS2 / PEG.
[0084] Example 6
[0085] A method for preparing a modified molybdenum disulfide / carbon-based composite material comprises the following steps:
[0086] S1. Dissolve ammonium molybdate tetrahydrate and thiourea in water, stir evenly, and transfer to a high-pressure reactor. React at 180°C for 24 hours. After cooling to room temperature, wash the product with ethanol and water and vacuum dry it at 60°C for 12 hours to obtain MoS2 powder.
[0087] Among them, the mass ratio of ammonium molybdate tetrahydrate:thiourea:water is 1.2:2.2:35.
[0088] S2. Preparation of low-defect MoS2: In a tubular furnace, under a nitrogen atmosphere, the temperature was 400°C, the gas flow rate was 20 mL / min, and the annealing time was 2 h.
[0089] S3. The low-defect MoS2 and the acidified carbon nanotubes were uniformly dispersed by ultrasonic dispersion with ethanol, and the PEM was dissolved with water. Then the PEM solution was slowly poured into the mixed dispersion of MoS2 and the acidified carbon nanotubes. After stirring at room temperature for 30 minutes, a PEM-modified MoS2 / carbon nanotube composite film was obtained.
[0090] Among them, the mass ratio of MoS2:PEM:acidified carbon nanotubes is 1:1:9, and the specific amounts of the three are 0.1g, 0.1g, and 0.9g respectively; the amount of ethanol used is 40ml, and the amount of water used is 20ml; and the ultrasonic time is 30min.
[0091] S4. Pour the PEM-modified MoS2 / carbon nanotube dispersion onto a polytetrafluoroethylene surface dish and allow it to dry naturally at room temperature to obtain a flexible PEM-modified MoS2 / carbon nanotube composite film, denoted as CNTs / MoS2 / PEM.
[0092] Example 7
[0093] The present invention is basically the same as Example 1, except that the annealing temperature of MoS2 powder is increased to 500°C.
[0094] A method for preparing a modified molybdenum disulfide / carbon-based composite material comprises the following steps:
[0095] S1. Dissolve ammonium molybdate tetrahydrate and thiourea in water, stir evenly, and transfer to a high-pressure reactor. React at 180°C for 24 hours. After cooling to room temperature, wash the product with ethanol and water and vacuum dry it at 60°C for 12 hours to obtain MoS2 powder.
[0096] Among them, the mass ratio of ammonium molybdate tetrahydrate:thiourea:water is 1.2:2.2:35.
[0097] S2. Preparation of low-defect MoS2: In a tubular furnace, under a nitrogen atmosphere, the temperature was 500°C, the gas flow rate was 20 mL / min, and the annealing time was 2 h.
[0098] S3. The low-defect MoS2 and the acidified carbon nanotubes were uniformly dispersed by ultrasonication with ethanol, and polyacrylic acid was dissolved in water. Then the polyacrylic acid solution was slowly poured into the mixed dispersion of MoS2 and the acidified carbon nanotubes. After stirring at room temperature for 30 minutes, the PAA-modified MoS2 / carbon nanotube dispersion was obtained.
[0099] Among them, the mass ratio of MoS2:PAA:acidified carbon nanotubes is 1:1:9, and the specific amounts of the three are 0.1g, 0.1g, and 0.9g respectively; the amount of ethanol used is 40ml, and the amount of water used is 20ml; and the ultrasonic time is 30min.
[0100] S4. Pour the PAA-modified MoS2 / carbon nanotube dispersion onto a polytetrafluoroethylene surface dish and allow it to dry naturally at room temperature to obtain a flexible PAA-modified MoS2 / carbon nanotube composite film, recorded as 2-CNTs / MoS2 / PAA.
[0101] Comparative Example 1 (MoS2 / carbon nanotubes)
[0102] A method for preparing a molybdenum disulfide / carbon-based composite material comprises the following steps:
[0103] S1. Dissolve ammonium molybdate tetrahydrate and thiourea in water, stir evenly, and transfer to a high-pressure reactor. React at 180°C for 24 hours. After cooling to room temperature, wash the product with ethanol and water and vacuum dry it at 60°C for 12 hours to obtain MoS2 powder.
[0104] Among them, the mass ratio of ammonium molybdate tetrahydrate:thiourea:water is 1.2:2.2:35.
[0105] S2. Preparation of low-defect MoS2: In a tubular furnace, under a nitrogen atmosphere, the temperature was 500°C, the gas flow rate was 20 mL / min, and the annealing time was 2 h.
[0106] S3. The low-defect MoS2 and the acidified carbon nanotubes are uniformly dispersed by ultrasonication using a 1:1 ethanol / water mixed solution to obtain a MoS2 carbon nanotube dispersion.
[0107] Among them, the mass ratio of MoS2: acidified carbon nanotubes is 1:9, and the specific amounts of the two are 0.1g and 0.9g respectively; the amount of ethanol used is 10ml, and the amount of water used is 10ml; the ultrasonic time is 30min.
[0108] S4. Pour the MoS2 / carbon nanotube dispersion onto a polytetrafluoroethylene surface dish and allow it to dry naturally at room temperature to obtain a MoS2 / carbon nanotube composite film.
[0109] Comparative Example 2 (PAA / carbon nanotubes)
[0110] A method for preparing a PAA / carbon-based composite material comprises the following steps:
[0111] S1. PAA and acidified carbon nanotubes are uniformly dispersed by ultrasonication using a 1:1 ethanol / water mixed solution to obtain a PAA / carbon nanotube dispersion.
[0112] Among them, the mass ratio of PAA: acidified carbon nanotubes is 1:9, and the specific amounts of the two are 0.1g and 0.9g respectively; the amount of ethanol used is 10ml, and the amount of water used is 10ml; and the ultrasonic time is 30min.
[0113] S2. Pour the PAA / carbon nanotube dispersion onto a polytetrafluoroethylene surface dish and allow it to dry naturally at room temperature to obtain a flexible PAA / carbon nanotube composite film, denoted as CNTs / PAA.
[0114] Comparative Example 3 (PEM / carbon nanotubes)
[0115] A method for preparing a PEM / carbon-based composite material comprises the following steps:
[0116] S1. PEM and acidified carbon nanotubes are uniformly dispersed by ultrasonication in a 1:1 ethanol / water mixed solution to obtain a PEM / carbon nanotube dispersion.
[0117] Among them, the mass ratio of PEM: acidified carbon nanotubes is 1:9, and the specific amounts of the two are 0.1g and 0.9g respectively; the amount of ethanol used is 10ml, and the amount of water used is 10ml; and the ultrasonic time is 30min.
[0118] S2. Pour the PEM / carbon nanotube dispersion onto a polytetrafluoroethylene surface dish and allow it to dry naturally at room temperature to obtain a flexible PEM / carbon nanotube composite membrane, denoted as CNTs / PEM.
[0119] Comparative Example 4 (PVA / carbon nanotubes)
[0120] A method for preparing a PVA / carbon-based composite material comprises the following steps:
[0121] S1. PVA and acidified carbon nanotubes are uniformly dispersed by ultrasonication in a 1:1 ethanol / water mixed solution to obtain a PVA / carbon nanotube dispersion.
[0122] Among them, the mass ratio of PVA: acidified carbon nanotubes is 1:9, and the specific amounts of the two are 0.1g and 0.9g respectively; the amount of ethanol used is 10ml, and the amount of water used is 10ml; and the ultrasonic time is 30min.
[0123] S2. Pour the PVA / carbon nanotube dispersion onto a polytetrafluoroethylene surface dish and allow it to dry naturally at room temperature to obtain a flexible PVA / carbon nanotube composite film, denoted as CNTs / PVA.
[0124] Since the properties of the modified molybdenum disulfide / carbon-based composite materials prepared in Examples 1 to 7 of the present invention are basically the same, the following tests are based on some examples.
[0125] Electrochemical test method:
[0126] The electrochemical tests were performed at room temperature in a three-electrode configuration connected to an electrochemical workstation, with Ag / AgCl and graphite rod as the reference electrode and counter electrode, respectively.
[0127] The preparation steps of the working electrode are as follows: Use a punch to take a small disc with a diameter of 4 mm from the MoS2 / PAA / carbon nanotube film, and weigh it to be 0.3 mg. Use 2 μL of 5 wt% nafion solution to load the catalyst on a rotating disk electrode with a diameter of 4 mm, and the loading amount is about 2.4 mg cm -2 .
[0128] HER tests were performed using linear sweep voltammetry (LSV) and rotating disk electrode (RDE) measurements at a scan rate of 5 mV / s and a rotation speed of 2500 rpm in 1 M KOH electrolyte. Before HER tests, the electrolyte was purged with N2 at room temperature.
[0129] Figure 1 This is a transmission electron microscope image of the PAA-modified MoS2 / carbon nanotube composite film after secondary ultrasonic dispersion obtained in Example 1 of the present invention. In the image, the dark black is molybdenum disulfide, the light black is acidified carbon nanotubes, and the water-based polymer is not displayed; it can be seen that the molybdenum disulfide particles are entangled and coated in the acidified carbon nanotubes.
[0130] Figure 2 The Raman spectra of the PAA-modified MoS2 / carbon nanotube composite film and carbon nanotube prepared in Example 1 of the present invention and the MoS2 / carbon nanotube prepared in Comparative Example 1. After the acidified carbon nanotubes and molybdenum sulfide are composited, an obvious peak change appears in the G band, indicating that there is a certain surface interaction between the two; while the addition of PAA does not bring about such a change, indicating that the role of PAA is more to improve the non-structural properties such as the hydrophilicity and hydrophobicity of the system surface.
[0131] Figure 3 The infrared spectra of composite materials prepared from different groups; The vibration mode of molybdenum disulfide is very special. Its eight sulfur atoms form an octahedral structure perpendicular to the plane, and two of the sulfur atoms show rotational symmetry in the crystal. This special structure will cause molybdenum disulfide to have almost no obvious absorption peak in the infrared spectrum, making it difficult to detect. Therefore, infrared characterization was not performed on the samples containing molybdenum sulfide: PAA-modified MoS2 / CNTs, PEG-modified MoS2 / CNTs, PVA-modified MoS2 / CNTs, and PEM-modified MoS2 / CNTs.
[0132] Figure 4The contact angles of the self-supporting films of acidified CNTs pressed film (a), PEG-modified MoS2 / CNTs composite film (b), PAA-modified MoS2 / CNTs composite film (c), PVA-modified MoS2 / CNTs composite film (d), and PEM-modified MoS2 / CNTs composite film (e). It can be seen that the contact angles of the self-supporting films of the modified MoS2 / carbon-based composite materials are all reduced, indicating that the modified MoS2 / carbon-based composite materials are more hydrophilic.
[0133] Figure 5 Actual picture of PAA-modified MoS2 / carbon nanotube composite film.
[0134] Figure 6 This is a test diagram of the flexibility of the PAA-modified MoS2 / carbon nanotube composite film. Figure 6 It can be seen that the PAA-modified MoS2 / carbon nanotube composite film provided by the present invention has very good flexibility and is not prone to cracking after bending.
[0135] Figure 7 The Tafel plot of the electrocatalytic hydrogen evolution of the PAA-modified MoS2 / carbon nanotube composite film in 1M KOH. As can be seen from the figure, the performance of the self-supporting flexible light-assisted electrocatalytic hydrogen production samples with different components is compared. After the component ratio is optimized, see Example 7, that is, 2-CNTs / MoS2 / PAA can achieve the best light-assisted electrocatalytic performance. Because the film-forming property of the molybdenum disulfide / carbon nanotube composite material is extremely poor without the addition of polymer, it is impossible to construct a self-supporting material electrode, and the performance can only be characterized by steady-state testing.
[0136] Figure 8 The photoresponse diagram of PAA-modified MoS2 / carbon nanotube composite film and MoS2 / carbon nanotube composite material. It can be seen from the figure that the addition of PAA increases the overall hydrogen production efficiency of the PAA-modified MoS2 / carbon nanotube composite film by about 40% at the same potential (180mV); compared with the non-illumination, the electrochemical catalytic performance of the PAA-modified MoS2 / carbon nanotube composite film under illumination is improved by about 7% to 10%.
[0137] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0138] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A modified molybdenum disulfide / carbon-based composite material, characterized in that: Include: Entangled carbon-based materials; Low-defect MoS2 is embedded inside and on the surface of the entangled carbon-based material, and the surface of the entangled carbon-based material is partially coated with a hydrophilic polymer.
2. A method for preparing the modified molybdenum disulfide / carbon-based composite material according to claim 1, characterized in that: Include: After the low-defect MoS2 and the entangled carbon-based material are evenly mixed, a hydrophilic polymer solution is added, and after stirring at room temperature for 30 minutes, the modified molybdenum disulfide / carbon-based composite material is obtained by drying.
3. The method for preparing the modified molybdenum disulfide / carbon-based composite material according to claim 2, characterized in that: The mass ratio of the MoS2:entangled carbon-based material:hydrophilic polymer is 1:9:
1.
4. The method for preparing the modified molybdenum disulfide / carbon-based composite material according to claim 2, characterized in that: The hydrophilic polymer is polyacrylic acid, polyethylene glycol, polyvinyl alcohol, or polyethylene glycol maleic anhydride ester.
5. The method for preparing the modified molybdenum disulfide / carbon-based composite material according to claim 2, characterized in that: The entangled carbon-based material is acidified carbon nanotubes, carbon cloth or carbon paper.
6. The method for preparing the modified molybdenum disulfide / carbon-based composite material according to claim 2, characterized in that: The preparation method of the low-defect MoS2 is: In a nitrogen atmosphere, MoS2 is annealed at 300-500°C for 1-3h to obtain the low-defect MoS2.
7. The method for preparing the modified molybdenum disulfide / carbon-based composite material according to claim 6, characterized in that: The gas flow rate of the nitrogen gas is 10 to 30 mL / min.
8. The method for preparing the modified molybdenum disulfide / carbon-based composite material according to claim 2, characterized in that: The low-defect MoS2 and the entangled carbon-based material are ultrasonically mixed, and the ultrasonic conditions are: 30 to 45 minutes, power 0.5 to 1.5 W / cm 2 .
9. Use of the modified molybdenum disulfide / carbon-based composite material according to claim 1 in light-assisted electrocatalytic hydrogen production.
